Talent Management: An Overview of Concept, Perspectives, Strategies & Challenges - Sengupta , SB (Gyan Management Journal, 2010)
In this paper, an attempt has been made to illustrate the concept of Talent Management evolved over time, and how it is viewed differently by different organizations and what are the researchers' different perspectives of talent management. The different focal areas and strategic approach for talent management that are being adopted currently by researchers is discussed, which is followed by a discussion on the current scenario of talent management in industry, and how it is expected to progress from a non-existent level to one which will be fully integrated with the corporate strategy. Lastly, the challenges faced by organizations during implementation of talent management process are discussed in the article.
Keywords: People; Retention; Development; Perspectives; Strategy